2010
DOI: 10.3324/haematol.2010.026401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of constitutional polymorphisms in VCAM1 and CD44 on CD34+ cell collection yield after administration of granulocyte colony-stimulating factor to healthy donors

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe number of CD34 + cells mobilized from bone marrow to peripheral blood after administration of granulocyte colony-stimulating factor varies greatly among healthy donors. This fact might be explained, at least in part, by constitutional differences in genes involved in the interactions tethering CD34 + cells to the bone marrow. Design and MethodsWe analyzed genetic characteristics associated with CD34 + cell mobilization in 112 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 43 publications
7
28
3
Order By: Relevance
“…This result could be confirmed by Bogunia-Kubik et al [39] and Ben et al [40]. Martin-Antonio et al [41] reported the same finding and observed associations between mobilization ability and even more polymorphisms, including VCAM-1 und CD44. An analysis of our group could not show a significant association of the CXCL12-3′A allele with more efficient stem cell mobilization in 463 unrelated donors (Schmidt J, Bornhäuser M et al, submitted).…”
Section: G-csf Dosing and Factors Affecting Mobilization Efficacysupporting
confidence: 78%
“…This result could be confirmed by Bogunia-Kubik et al [39] and Ben et al [40]. Martin-Antonio et al [41] reported the same finding and observed associations between mobilization ability and even more polymorphisms, including VCAM-1 und CD44. An analysis of our group could not show a significant association of the CXCL12-3′A allele with more efficient stem cell mobilization in 463 unrelated donors (Schmidt J, Bornhäuser M et al, submitted).…”
Section: G-csf Dosing and Factors Affecting Mobilization Efficacysupporting
confidence: 78%
“…However, we still observed vesicle transfer from CB-NK to MM cells and also secondary transfer between MM cells (Figure 7b). Because CXCL12 tethers hemopoietic cells into the stroma, 28 we measured CXCL12 secretion by the stroma and observed a reduced CXCL12 secretion after the addition of MM cells or MM cells and CB-NK (Figure 7c, Po0.05), suggesting a possible role for CXCL12 in reducing the anti-MM cytotoxicity of CB-NK. Therefore we performed cytotoxicity assay adding AMD3100, which inhibits binding of CXCL12 to CXCR4 in hemopoietic cells.…”
Section: Nkg2d Expression In MM Cells After Cb-nk Treatmentmentioning
confidence: 99%
“…RNA isolation was performed as previously described. 18 Real-time RT-PCR analysis for all the genes but P53 was carried out using the 7900HT Fast Real-Time PCR System (Applied Biosystems). For P53, real time RT-PCR reactions were done in a 25-mL volume containing complementary DNA generated from 10 ng of original RNA template, 300 nM each of specific forward and reverse primers (p53Fw: 5 0 -GCCCACTTCACCGTACTAACC-3 0 and p53Rv: 5 0 -GCCCAA CTGTAGAAACTACCA-3 0 ) and 12.5 mL of iQ-SYBR Green Supermix (Bio-Rad, Hercules, CA, USA).…”
Section: Functional Studiesmentioning
confidence: 99%